STAND VOLUME EQUATION FOR Pinus brutia Ten. NATURAL GROWING IN ZAWITA AREA, KURDISTAN REGION OF IRAQ - HASAN, SILAV SADEEQ; HAJI , GHARIBA Y.; HASSAN , MOHAMMAD K. (Journal of Duhok University, 2022)
Calabrian pine (Pinus brutia Ten.) is grown naturally in Zawita area, Kurdistan Region of Iraq.  It is preferable to have stand volume equation specifically for natural stand of this species due to its importance in decision making regarding many forest management problems. In this work, a reliable stand volume equation was developed for this species to fill this gap. The developed equation was found to be in accord with the least square assumptions. As was the case with many stand volume models that have been developed for different species, stand basal area and stand height were the best in explaining the variation in stand volume. A stand volume table was presented to instantly estimate stand volume from combinations of stand basal area and stand height